Improving Emerging Markets Healthcare through Private Provision - Walton, Tom (International Finance Corporation, Washington, DC, 2018)
The role of private enterprise in healthcare is to complement and support improvements to public healthcare, not to supplant it. Private providers are the primary source of care for the world’s poorest people and their record is often as good as or better than that of public providers. As low and middle-income economies grow and resources become more widely available, competition and consumer choice offer substantial potential to improve the reach, quality, and efficiency of both private and public provision.